The Validation of Learning Devices Based on Cognitive Conflict Approach in Blended Learning Model - Martina Nur Larasafitri; Gunawan Gunawan; Kosim Kosim (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to describe validation of learning devices based on cognitive conflict approach in blended learning model. The learning devices are developed to improve students’ concept mastery and critical thinking ability. The learning devices are lesson plans (RPP), learning materials, student worksheet, and evaluation instruments. This study is a research and development using 4-D model, define, design, develop, and disseminate. This study is focus on develop stage. Validation process is done in develop stage. Validation process is using instrument (validation sheet). The validity of the learning devices was assessed by 3 experts who are competent at Mataram University. Criticisms and suggestions given by validators are used as improvements to developed learning devices. Data analysis is about the validity and reliability (percentage of agreement). The results said learning devices is very suitable for learning. The results of agreement between validators showed developed learning devices scored more than 75% which included in reliable category. More complete and detail explanation about validation results is presented in this article